Implementation of Group Exchange Learning Model in The Subject Muthala’ah at Madrasah Aliyah Al-Umm Malang - Naufal Fikri; Muasshomah Muasshomah; Muhammad Safari; Shafrul Fajri (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
The aim of this study is to reveal the application of the learning model "Group of Group Exchange" in the subject "Muthala'ah" at Madrasah Aliyah Al-Umm Malang and express the impressions of students by using the learning model "Group of Group Exchange" to make students active and increase in learning Arabic. This research uses   field research with a qualitative descriptive type, and researchers also use three methods to collect data, namely: observation, interviews, and written documents. The results showed that (1) The use of the "Group of Group Exchange" learning model in the "Muthala'ah" subject at Madrasah Aliyah Al-Umm Malang: made students more active because during class students discussed and presented learning outcomes. Group discussion on four topics namely think before you decide, cleanliness, stingy people and take your chances. (2) There is an increase in class interest in understanding reading material, and makes students more enthusiastic during the learning process, as well as the emergence of interaction, effort, and participation between students in understanding the text distributed by the teacher during the learning process in class.